Studying Waiting Time of Patient during Discharge Process in Clinical Departments of Imam Reza Hospital affiliated with Mashhad University Of Medical Science In 2014 - hosein ebrahimipour; ali vajaee; gholam-abas nouri; habib-allah esmaeili; sara jamili (Tehran University of Medical Sciences, 2015)
Background: Process of discharging patients affects patient's satisfaction .This is one of the serious challenges that hospital managers face. This study is aimed to determine the average waiting time of patient discharge process and identify influential factors of this process in Imam Reza Hospital in Mashhad in the year of 2014. Materials & Methods: This is a cross-sectional survey in which waiting time of patients who had discharged from clinical wards of the Imam Reza hospital in Mashhad had been studied. 455 of patients had been selected as samples. The amount of  time spent during discharge in six different departments  such as inside each ward, from each ward to the medical records unit, inside the medical records unit, from medical records unit to  accounting department , during cost calculation and also from  cost accounting to cost payment unit) had been determined by using stop-watch method. The data had been analyzed by descriptive and analytical statistics in significant level of 0.05  using SPSS16. Results: Results showed that waiting time was 504.26± 362.96 Minutes. Patients spent most and least proportion of their waiting time in ENT and Burns wards during discharge. Conclusion:   As noticeable number of minutes spent inside wards and cost payment unit by patients, calls for corrective interventions such as changing visit time and predicting schedules for sending medical record to accounting department could  reduce waiting time.